Neutrality in the Face of Reckless Hate : Wikipedia and GamerGate - Salor, Enrinc (Nordisk Tidsskrift for Informationsvidenskab og Kulturformidling, 2016)
The year 2015 will very likely be remembered as a turning point in video game industry and culture. While tensions were slowly escalating regarding diversity of representation in video games across the cultural sphere and the position and treatment of women and other minorities within the industry, these insular debates finally, and violently, broke into mainstream consciousness in the second half of 2014. As we grimly note the one-year anniversary of the birth of the amorphous movement called GamerGate, the games industry is showing slow but hopeful signs of change regarding inclusion and representation of gender and ethnic diversity. Meanwhile, since GamerGate as a movement strives to achieve its self-declared goal of "ethics in video game journalism" primarily through constant and brutal harassment of women across the cultural space of games, their frequent targets are slowly and painfully trying to rebuild their lives.